2011
DOI: 10.1103/physrevb.84.024111
|View full text |Cite
|
Sign up to set email alerts
|

Zircon to monazite phase transition in CeVO4: X-ray diffraction and Raman-scattering measurements

Abstract: X-ray diffraction and Raman-scattering measurements on cerium vanadate have been performed up to 12 and 16 GPa, respectively. Experiments reveal that at 5.3 GPa the onset of a pressure-induced irreversible phase transition from the zircon to the monazite structure. Beyond this pressure, diffraction peaks and Raman-active modes of the monazite phase are measured. The zircon to monazite transition in CeVO 4 is distinctive among the other rare-earth orthovanadates. We also observed softening of external translati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 67 publications
9
45
1
Order By: Relevance
“…The refined unit-cell parameters for these phases are a = 7.377(7) Å and c = 6.485(6) Å for CeVO 4 and a = 7.166(7) Å and c = 6.317(6) Å for TbVO 4 . These values are in agreement with earlier reported values [6,14].…”
Section: Methodssupporting
confidence: 94%
See 2 more Smart Citations
“…The refined unit-cell parameters for these phases are a = 7.377(7) Å and c = 6.485(6) Å for CeVO 4 and a = 7.166(7) Å and c = 6.317(6) Å for TbVO 4 . These values are in agreement with earlier reported values [6,14].…”
Section: Methodssupporting
confidence: 94%
“…We have analyzed the volume changes using a thirdorder Birch-Murnaghan EOS [28]. The obtained EOS parameters for zircon phase are: In previous studies it has been reported that both the scheelite and monazite structures can be achieved in CeVO 4 upon compression [6,30]. In our case, in an experiment preformed under nearly hydrostatic conditions, the diffraction patterns of the HP phase can be undoubtedly assigned to the monoclinic monazite-type structure.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, the pressures at which the phase transitions occur could differ a bit from those observed experimentally, as it has been reported in other compounds, where these effects are demonstrated to be relevant. 56,57 According to the H versus P diagram, at 0 K, we found that under hydrostatic conditions the phase transition driven by pressure can be summarized as follows: rutile → CaCl 2 type → distorted PdF 2 type → distorted fluorite → cotunnite, which is similar to the transitions reported in other TMF 2 compounds such as FeF 2 (Ref. 10) and MnF 2 .…”
Section: Structural Propertiessupporting
confidence: 83%
“…A second issue that 3 deserves to be addressed is the influence of deviatoric stresses on the HP structural sequence; these stresses have been shown to considerably influence the HP structural behavior of the isomorphic HoVO 4 and CeVO 4 [14,28]. Other facts that should be explored in detail are the possible decomposition or amorphization of EuVO 4 .…”
Section: Introductionmentioning
confidence: 99%